Evaluation of the compostability and toxic effects on Hordeum vulgare and Cynodon dactylon plants of plastic bags manufactured with compostable plastics - Erik Saúl Huidobro-Medina; María Neftalí Rojas-Valencia (PLoS ONE, 2025)
Because of the problem related to the accumulation of plastic bags in the environment, polymers called “bioplastics” have been developed. These materials are designed to reintegrate quickly into the environment, reducing thus environmental damage. However, when testing disposable bags made with biopolymers using standardized methodologies, it has not been possible to observe that they satisfactorily meet the criteria to be considered compostable. The present study evaluated compliance with the compostability criteria according to international standards established by the International Organization for Standardization (ISO) of three certified compostable plastic bags (BioW, Comph and Ecol) manufactured with polybutylene adipate-co-terephthalate, polylactic acid and corn starch, performing chemical composition tests using attenuated total reflectance Fourier Transform infrared (ATR-FTIR) spectroscopy and inductively coupled plasma – optical emission spectroscopy (ICP-OES), and disintegration, biodegradation and ecotoxicity tests. The results showed that the three bags contain the polymers reported in their data sheet and possibly polyethylene. Likewise, all of them comply with the maximum permissible limit of metals. Comph and Ecol met the disintegration criteria. No bag met the aerobic biodegradation criterion, with Ecol showing the highest percentage (51%) and Comph the lowest (3%). None of the bags had toxic effects on plants and neither met the biodegradation criterion necessary to be considered 100% compostable.